English Language Learning in Elementary School by Means of Digital Storytelling: The StoryTimE-Project - Caroline Theurer; Maria Eisenmann; Katharina Kindermann; Sanna Pohlmann-Rother (CLELEjournal, 2024)
This article draws on a digital storytelling approach. The authors describe a pilot study that aimed to activate young learners' own English language production through collaborative story creation using tablets.